Product Differentiation, Market Orientation, and Product Quality Against Competitive Advantage in UMKM Rotan Desa Trangsan, Gatak, Sukoharjo - Utami, Raras; Istiatin, Istiatin; Suryo, Ibnu (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
UMKM are one of the leading economic drivers in economic development in a country. This research was conducted in Desa Trangsan, Gatak, Sukoharjo. This study aimsi to determine the effect lof product differentiation, marketi orientation, a lproduct quality on competitivei advantagej in UMKM Rattan in Desa Trangsan, Gatak, Sukoharjo. This research method uses quatitative methods. The population is UMKM Rattan in Desa Trangsan is 210 and using a sample 58 respondents. Purposivei samplingi is a sampling techniquel withl the criteria ofi a business that 5 years, is actively producing, and its products have participated in the international market. The data analysis used is using multiplei linearl regression, oF-test,pt-test fand the coefficientl of determinationi through SPSSl v20. Thei results lof the analysis of thisl tstudy lindicate that product differentiation, lmarket iorientation, and product quality lhave a significantj and positive effect on competitive advantage with coefficient of l64,1%. Whiles thei remaining. 35,1% is linfluenced lby otherl factor or variablesl not examined ini this lstudy. Keywordsi: Product Differentiation, Market Orientation, Product Quality, and Competitive Advantage